EUS-guided radiofrequency ablation of pancreatic/peripancreatic tumors and oligometastatic disease: an observational prospective multicenter study - Figueiredo Ferreira, Mariana; Garces-Duran, Rodrigo; Eisendrath, Pierre; Devière, Jacques; Deprez, Pierre; Monino, Laurent; Van Laethem, Jean-Luc; Borbath, Ivan (Endoscopy International Open, 2022)
Background and study aims Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) is an emerging and minimally invasive technique that seems promising for treatment of focal pancreatic and peripancreatic lesions. Our aim was to prospectively evaluate the feasibility, safety, and technical and clinical success of pancreatic and extra-pancreatic EUS-RFA.Patients and methods We prospectively collected clinical and technical data for all patients who underwent EUS-RFA at two Belgian academic centers from June 2018 to February 2022. Feasibility, adverse events (AEs), and follow-up were also assessed.Results Twenty-nine patients were included, accounting for 35 lesions: 10 non-functioning neuroendocrine tumors (29 %), 13 pancreatic insulinomas (37 %), one adenocarcinoma (3 %), and 11 intra-pancreatic and extra-pancreatic metastatic lesions (31 %). Technical success was achieved in 100 % of cases, with a median of three power applications per lesion (interquartile range 2). The majority of patients (59 %) presented no collateral effects, three (10.3 %) developed non-severe acute pancreatitis, and four (14 %) had mild abdominal pain. At 6 months follow-up (n = 25), 36 % of patients showed radiological complete response, 16 % presented a significant partial response and 48 % showed < 50 % decrease in diameter. At 12 months (n = 20), 30 % showed complete necrosis and 15 % > 50 % decrease in diameter. Hypoglycemia related to insulinoma was immediately corrected in all 13 cases, with no recurrence during follow-up.Conclusions EUS-RFA is feasible, safe, and effective for treatment of pancreatic and peripancreatic tumors. Larger and longer multicenter prospective studies are warranted to establish its role in management of focal pancreatic lesions and oligometastatic disease. Symptomatic insulinoma currently represent the best indication.